Harnessing Development Communication for Urban Growth: Evaluating Strategic Communication in Infrastructure and Social Development in the Federal Capital Territory, Abuja - Adamu, Ngbede Adamu; Dantawaye, Gajere Miller Dantawaye; Abwami, Innocent Michael Abwami (African Journal of Stability and Development (AJSD), 2025)
This paper examines the role of development communication in driving infrastructural growth and socio-economic development in Abuja, Nigeria’s capital city. It highlights how strategic communication initiatives have facilitated public participation, improved policy implementation, and fostered collaboration between stakeholders in urban development projects. Drawing from various case studies, the paper explores the effectiveness of media campaigns, community engagement programmes, and digital communication platforms in promoting sustainable development. Despite notable progress, challenges such as inadequate communication infrastructure, low media literacy, and political interference persist. The paper concludes by recommending enhanced investment in development communication, capacity building for communication practitioners, and the adoption of innovative communication technologies to support Abuja’s development agenda. The study highlights the crucial role of communication in shaping urban development, advocating for more inclusive, transparent, and participatory communication strategies in Nigeria’s development efforts.